Cultural Communications of Islamic Boarding Schools in Indonesia - Ujang Saepullah (AL-ISHLAH: Jurnal Pendidikan, 2021)
Pesantren communication culture is quite distinct from other cultures, as it has its own unique, unique, and distinct culture. The santri's obedience, sincerity, and respect for the Kyai exemplify its uniqueness. The author attempts to raise this unique communication culture as a research theme by researching a salaf (traditional) Islamic boarding school, An-Nidzam Sukabumi, and a modern Islamic boarding school, Pondok Pesantren Kholaf (modern) Assalam Sukabumi. The research focuses on the unique characteristics of each of the two Islamic boarding schools. This study employs a qualitative approach based on ethnographic methods because it is highly relevant to its focus on the language spoken, communication patterns observed, and communication culture of pesantren. The findings indicated that the communication cultures of the salaf and Khalaf pesantren were significantly different. The An Nizam salaf pesantren placed a premium on regional/Sundanese languages in daily interactions while simultaneously suppressing learning in religious sciences from the yellow books. The Kalaf/modern Assalam Islamic boarding schools placed a premium on Arabic and English instruction. The use of English in daily interactions and an understanding of the spiritual sciences are explored through classically taught contemporary books.